Self-censorship in social networking sites (SNSs) – privacy concerns, privacy awareness, perceived vulnerability and information management. Issue 4 (11th November 2019) - Warner, Mark; Wang, Victoria
Abstract : Purpose: This paper aims to investigate behavioural changes related to self-censorship (SC) in social networking sites (SNSs) as new methods of online surveillance are introduced. In particular, it examines the relationships between SC and four related factors: privacy concerns (PC), privacy awareness (PA), perceived vulnerability (PV) and information management (IM). Design/methodology/approach: A national wide survey was conducted in the UK ( N = 519). The data were analysed to present both descriptive and inferential statistical findings. Findings: The level of online SC increases as the level of privacy concern increases. The level of privacy concern increases as the levels of PA and PV increase and the level of effective IM decreases. Originality/value: This study extends the literature on online SC, showing that PCs increase the level of SC in SNSs. It provides support for three antecedent factors to PC which impact upon levels of SC when communicating in SNSs.